Pre-Service Early Childhood Educators' Leadership Development through Reflective Engagement with Experiential Service Learning and Leadership Literature. Issue 4 (December 2014) - Diamond, Alexandra
THIS STUDY INVESTIGATED WHETHER final-year early childhood education students' aspirations for professional leadership roles, and positive perceptions of themselves as leaders, improved through engagement in a university course requiring reflection on service learning leadership projects, and leadership and advocacy literature. Before and after surveys found students' leadership self-perceptions and aspirations significantly improved on completing the course. Thematic analysis of students' reflections found initial notions about leadership were narrower, and more focused on positional power and stereotypically male capabilities than at the end of the course. Improved leadership self-perceptions and aspirations arose from leadership self-audits, participation in service learning (in which students practised leadership skills, challenged themselves, wrestled with difficulties, and discussed progress and strategies with other stakeholders), reflection on their current and aspirational leadership capabilities, and utilisation of leadership and advocacy literature to inform actions and reflections. Findings suggest these combined elements can support early childhood leadership development.